Biodiesel production from waste cooking oil using bifunctional heterogeneous solid catalysts - Farooq, M. (2013)
In the present work, bifunctional heterogeneous catalysts were studied to develop an effective catalyst for biodiesel production from waste cooking oil with improved catalytic activity and stability. The catalysts were characterized by various analytical techniques to explore their physicochemical properties. The catalytic activity was evaluated in the transesterification of waste cooking oil for low cost biodiesel production. The bifunctional heterogeneous catalysts show improved transesterification activities. Among the different catalysts tested, the Mo-Mn/Î³-Al2O3-15 wt MgO catalyst provides the maximum biodiesel yield of 91.4 in reaction time of 4 h at reaction temperature of 100 C, methanol to oil molar ratio of 27:1 and an agitation speed of 500 rpm. Moreover, the bifunctional heterogeneous catalyst shows substantial chemical stability and could be reused for at least eight times without major loss in its catalytic activity. The physicochemical properties of the biodiesel produced from waste cooking oil were further studied and compared with the ASTM and the EN biodiesel specifications. The results show that the properties of the biodiesel produced comply with the international standard specifications. Â© 2013 Elsevier Ltd. All rights reserved.